The Taxation of Stockholders - Crum, W. L. (Quarterly Journal of Economics, 1950)
I. Point of view, basic assumption, and source of data, 15. — II. Determination of average corporation tax rate, 20. — III. Rate of individual income tax, 22; (a) six broad categories, 23; (b) size classification, 24; (c) representativeness of the average taxpayer, 24; (d) average total income of a class, 27; (e) rates of tax on total income, 27; (f) rates on corporate net income, 32. — IV. Certain policy implications, 35; (a) two factors causing inequity, 36; (6) exploitation of stockholders having low net incomes, 40; (c) complete cure of inequity, realized-income basis, 43; (d) the taxation of income not realized by stockholders, 47; (e) taxing stockholders as partners, 50; (f) partial cures of inequity, 53.